Adverse pregnancy outcomes associated with first-trimester exposure to angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers: A systematic review and meta-analysis - Nida Buawangpong (2020)
© 2020 The Authors. Pharmacology Research & Perspectives published by British Pharmacological Society and American Society for Pharmacology and Experimental Therapeutics and John Wiley & Sons Ltd. This study aimed to determine the effects of prenatal exposure to angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin II receptor blockers (ARBs), particularly when exposure is limited to the first trimester of pregnancy, on adverse maternal and neonatal outcomes. A systematic search was performed on four databases, that is, PubMed, Scopus, Web of Science, and Cochrane Library, to identify relevant articles published up to December 31, 2019. Included studies were limited to original investigations assessing the association between prenatal exposure to ACEIs/ARBs and adverse pregnancy outcomes. Odds ratios were used as a summary effect measure. Pooled-effect estimates of each outcome were calculated by the random-effects meta-analysis. The main outcomes included overall and specific congenital malformations, low birth weight, miscarriage, elective termination of pregnancy, stillbirth, and preterm delivery. Of 19 included articles involving a total of 4 163 753 pregnant women, 13 studies reported an increased risk of, at least, one adverse pregnancy outcome in pregnant women who were exposed to ACEIs/ARBs. Meta-analysis revealed a significant association between overall congenital malformations and first trimester-only exposure to ACEIs/ARBs (OR = 1.94, 95% CI = 1.71-2.21, P < .0001). Cardiovascular malformations, miscarriage, and stillbirth also provided a significant relation with ACEI/ARB exposure. In conclusion, prenatal exposure to ACEIs/ARBs in the first trimester of pregnancy was found to be associated with an increased risk of adverse pregnancy outcomes. Women of reproductive age should be aware of the potential teratogenic risks of these drugs if they become pregnant.